ProcessM: Intelligent Process Mining software - Tomasz P. Pawlak; Jędrzej Potoniec (SoftwareX, 2025)
Contemporary software guides and executes various business processes, such as production, delivery of goods, sales, and official procedures. However, due to software flexibility, unforeseen circumstances, and exceptional conditions, processes may not always be executed as intended. Without proper monitoring, these deviations can go unnoticed. ProcessM is an open-source software designed for users with limited technical expertise specializing in business process analysis. It integrates with multiple database management systems to extract and transform data into event logs, and monitor databases for new events. ProcessM generates process models in standard representations like BPMN and tracks changes in processes. It also calculates Key Performance Indicators (KPIs), breaking them down by individual activities and relationships. ProcessM is designed for auditing, decision-making, and operations management across industries.